Simulação numérica de laminação a frio no laminador sendzimir número 2 da acesita - Carlos Lovato Neto (2006)
This work presents a study of the application of the method of finite elements for the simulation of the Sendzimir cold rolling number 2 of the Acesita for silicon steel of grain not oriented. To determine the material flow curve the Ford test was used, and for determination of the attrition coefficient it used measurements during the process. of torque, forward slip and roll force. The simulation was validated comparing its values ofroll force and forward slip with the collected ones in the equipment. Using the developed model it was simulated variation of the parameters of process and its effect in the cold rolling, as well as the influence of work roll with different diameters